2015
DOI: 10.1016/j.compositesa.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of inter-ply shear in uncured carbon fibre prepreg

Abstract: Understanding the inter-ply shear behaviour of uncured carbon fibre prepreg is fundamental to avoiding process-induced defects during manufacturing of largescale components. Shear tests for AS4/8552 are compared to a one-dimensional viscoelastic-plastic model for inter-ply shear. The paper presents a methodology capable of determining the parameters of temperature, rate and pressure required for minimum resistance to movement of a prepreg. Investigating the joint strength and friction values individually shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 15 publications
3
28
0
Order By: Relevance
“…This is marked by a change in friction response from one dominated by hydrodynamic lubrication to one dominated by boundary lubrication. A similar response is shown when it comes to the critical yield stress [19]. That is, τ c decreases upon heating, reaches a minimum value, and then increases again slightly.…”
Section: Pre-yield Behavioursupporting
confidence: 68%
See 3 more Smart Citations
“…This is marked by a change in friction response from one dominated by hydrodynamic lubrication to one dominated by boundary lubrication. A similar response is shown when it comes to the critical yield stress [19]. That is, τ c decreases upon heating, reaches a minimum value, and then increases again slightly.…”
Section: Pre-yield Behavioursupporting
confidence: 68%
“…The latter, j, highest within the hydrodynamic regime, begins at a maxima and decreases with an increase in temperature. Conversely, µ, highest during boundary lubrication, begins at a minima and increases with an increase in temperature [19]. These contradictory affects are related to the amount of surface resin present [19,28].…”
Section: Pre-yield Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of the friction coefficient was also investigated. Larberg and Akermo [52] and Erland et al [53] have shown that different but chemically similar prepreg systems can exhibit very dissimilar frictional behavior depending on the toughening strategy used (i.e., whether the thermoplastic particles are dispersed on the prepreg surface or not) and the processing conditions. Friction coefficients varying from g % 0 up to g ¼ 0:2 have been measured in the past.…”
Section: Interplymentioning
confidence: 99%